2022
DOI: 10.1108/apjml-01-2022-0050
|View full text |Cite
|
Sign up to set email alerts
|

Marketing competency, marketing innovation and sustainable competitive advantage of small and medium enterprises (SMEs): a mixed-method analysis

Abstract: PurposeThe purpose of the current research is to investigate the relationship between marketing capabilities and marketing innovation toward the sustainable competitive advantage of small and medium enterprises in the Philippines. The research study aims to improve the prior conducted literature by concentrating on the precursors of innovation in marketing and its impact on building a sustainable competitive market. The paper intends to address this by examining the following variables using a mixed-method app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Previously, marketing capability has also been found to have a positive effect on sustainable competitive advantage. However, other studies have reported no significant relationship between marketing capability and sustainable competitive advantage [7]. Overall, the relationship between innovation and marketing capabilities and sustainable competitive advantage is complex and multifaceted.…”
Section: Introductionmentioning
confidence: 87%
“…Previously, marketing capability has also been found to have a positive effect on sustainable competitive advantage. However, other studies have reported no significant relationship between marketing capability and sustainable competitive advantage [7]. Overall, the relationship between innovation and marketing capabilities and sustainable competitive advantage is complex and multifaceted.…”
Section: Introductionmentioning
confidence: 87%
“…Several case studies have focused on MSMEs in the Philippines, Indonesia, Mexico, and India. This study used quantitative and qualitative methods such as interviews, questionnaires, and Six Sigma (Hernández-Gracia & Duana-Avila, 2022;Kusumasari & Retnandari, 2021;Olazo, 2022). Many studies say that MSMEs must adopt technology and IT to achieve entrepreneurial goals.…”
Section: Requirement Of Msmesmentioning
confidence: 99%
“…Industry innovation has been shown to positively impact business performance, sustainable competitiveness, customer satisfaction, and behavioural loyalty (So et al, 2022). Previous studies have examined marketing innovation and its relationship to competitiveness (Olazo, 2022), as well as the impact of technological and service innovation on restaurant performance (Chattopadhyay & Shah, 2014;Supriadi et al, 2022) and overall innovativeness on business success (Tan et al, 2019). The role of innovation becomes evident in the context of starred restaurants, where it stimulates creation, enhances the quality of products and services, and contributes to a unique dining experience (Meneguel et al, 2019).…”
Section: Introductionmentioning
confidence: 99%